Optimizing contract drafting to unlock efficiency and enhance productivity - N/A, Micka Surya Jaya (Animo Repository, 2023)
This research project focuses on the importance of clear and easy-to-understand contracts for effective business operations and building strong relationships. It explores the challenges faced by people in global business settings when using contract templates and emphasizes the need for templates that consider different languages and cultures. The research aims to address these challenges by developing contract templates that improve communication and understanding among diverse groups. As a Finance Operations Specialist (Contract Drafter), participating in this research offers personal and professional benefits, like expanding knowledge in financial operations and dispute prevention. The research outcomes provide practical solutions and encourage ongoing improvements in the organization. Key recommendations include giving priority to templates in multiple languages, standardizing processes, providing training for contract drafters, and establishing feedback systems to improve contract quality and overall performance. The project also highlights the value of using research methods in management education to equip future managers with problem-solving skills and a culture of continuous improvement. In the future, research in contract management can explore cultural and language factors and optimize different stages of the contract process to address specific challenges in different industries. Overall, this research project successfully achieved its goals, resulting in personal and professional growth for the researcher and setting the groundwork for further improvements and future research in contract management. The comprehensive framework and research principles led to significant improvements in the contract process, efficiency, and relationships with clients.